A text analysis of “The 2007 commencement speech by Bill Gates at Harvard University ” and “The 2014 commencement speech by Bill and Melinda Gates at Stanford University” on the De Beaugrande framework : M.A Thesis: - Nguyễn, Linh Chi (University of Languages and International Studies, 2017)
Electronic Resources